A comprehensive clinical review of maxillary sinus floor elevation: anatomy, techniques, biomaterials and complications. Issue 7 (September 2016) - Danesh-Sani, Seyed Amir; Loomer, Peter M; Wallace, Stephen S
Abstract: Several systematic reviews have shown that maxillary sinus augmentation is a predictable and effective procedure for augmentation of an atrophic posterior maxilla. However, we know of no reviews that have covered all the clinical aspects. We searched the PubMed, EMBASE, Cinhal, and Cochrane databases up to January 2015 to select relevant studies that cover the different objectives of this review, including the anatomy of the maxillary sinus, surgical techniques, biomaterials used in the sinus augmentation, and potential complications.